Pengaruh Humanistik dalam Perkembangan Belajar Anak - Saputri, Vica Septianti; Mawaddah, Sofi Arifiana; Deviyani , Deviyani (FKIP Universitas Islam Jember, 2024)
This study aims to present a review of the literature on the influence of a humanistic approach in the development of children's learning. The humanistic approach emphasizes the importance of understanding and respecting individuals in learning contexts, which can influence various aspects of child development. Through analysis of various relevant literature sources, this study identified several positive impacts of a humanistic approach on children's learning development, including increased intrinsic motivation, active involvement, deeper understanding of concepts, development of social skills, and increased learning independence. In addition, a humanistic approach can also improve the relationship between teachers and students, create an inclusive learning environment, and increase learning satisfaction. The results of this study can provide useful insights for educators, parents and education practitioners in understanding the importance of a humanistic approach in promoting holistic and sustainable learning development in children.